3D position sensing using the differences in the time-of-flights from a wave source to various receivers. - Mahajan, A. (IEEE Transactions on robotics and automation)
This paper presents a novel formulation for the estimation of the coordinates of a wave source based on the differences in the time-of-flights from a single transmitter to various receivers fixed in 3D space. The formulation is closed form linear, and estimates the speed of sound at every ranging operation. This leads to a robust system that is insensitive to changes in the environmental conditions. Typical applications that will benefit from this technology are 3D position sensing systems that may be used in robotics, navigation of autonomously guided vehicles, tracking of objects for virtual reality cells, and vibration analysis